Antithrombin III/SerpinC1 insufficiency exacerbates renal ischemia/reperfusion injury - Wang, Feng (Kidney Int, 2015)
Antithrombin III, encoded by SerpinC1, is a major anti-coagulation molecule in vivo and has anti-inflammatory effects. We found that patients with low antithrombin III activities presented a higher risk of developing acute kidney injury after cardiac surgery. To study this further, we generated SerpinC1 heterozygous knockout rats and followed the development of acute kidney injury in a model of modest renal ischemia/reperfusion injury. Renal injury, assessed by serum creatinine and renal tubular injury scores after 24 h of reperfusion, was significantly exacerbated in SerpinC1(+/−) rats compared to wild-type littermates. Concomitantly, renal oxidative stress, tubular apoptosis, and macrophage infiltration following this injury were significantly aggravated in SerpinC1(+/−) rats. However, significant thrombosis was not found in the kidneys of any group of rats. Antithrombin III is reported to stimulate the production of prostaglandin I(2), a known regulator of renal cortical blood flow, in addition to having anti-inflammatory effects and to protect against renal failure. Prostaglandin F1α, an assayable metabolite of prostaglandin I(2), was increased in the kidneys of the wild-type rats at 3 h after reperfusion. The increase of prostaglandin F1α was significantly blunted in SerpinC1(+/−) rats, which preceded increased tubular injury and oxidative stress. Thus, our study found a novel role of SerpinC1 insufficiency in increasing the severity of renal ischemia/reperfusion injury.